Validez discriminante, convergente/divergente, fiabilidad y consistencia interna, del whoqol-bref y el mossf-36 en adultos sanos de un municipio colombiano (2015)
ABSTRACT: Assessing quality of life is useful strategy to transcend the classical measurements of morbidity, mortality and disability. In Colombia its measurement focuses on the economical factors and some tools that provide a more holistic assessment have been evaluated. Objective: to evaluate the psychometric properties of the whoqol-bref and mossf-36 questionnaires with adults from a Colombian municipality. Methodology: a psychometric assessment and a cross sectional study conducted on 565 adults from the Rionegro municipality selected through probability sampling. The primary source of information was used and the analysis was performed with the SPSS21.0® and Epidat 3.0 software packages using frequencies and summary measures to describe the dimensions of the instruments. Similarly, Cronbach's α and Pearson correlation coefficients ewere usde to evaluate the psychometric properties. Results: the mean age was 51 years with a range between 20 and 94. Reliability was greater than 0.8 and the percentage of success in internal consistency and discriminant validity was 100% for all dimensions. The dimensions of both instruments showed statistically significant correlations above 0.4, demonstrating the convergent validity of the two scales. Conclusions: The WHOQOL-BREF and MOSSF-36 questionnaire had good psychometric performance, thus their application provides reliable and valid measures for assessing the quality of life of Colombian populations.